A PRODUCTION AND ECONOMIC ANALYSIS OF RASPBERRY AND ITS IMPACT ON THE SUSTAINABLE DEVELOPMENT OF RURAL AREAS: A SPECIAL FOCUS ON THE SITUATION IN THE SERBIA AND POLAND - Natasa Kljajic; Iwona Pomianek; Predrag Vuković (Ekonomika Poljoprivrede (1979))
Raspberry is Serbia’s most significant agro-industrial export, giving the country a competitive edge globally despite its smaller size and lower technological development. Over the past decade (2013–2022), raspberry production has faced challenges, including disputes over purchase prices between producers and cold store owners. The paper analyses global, European, and Serbian raspberry production, including yields, export/import data, and prices, with a comparison to Poland—another leading producer. Both countries have ideal conditions for high-yield raspberry farming, though production remains extensive in some areas. Serbia holds a top global position in frozen raspberry exports, and there is strong potential for growth, especially in fresh and organic raspberries. This requires government support, subsidies, and better use of natural and local resources to boost competitiveness and rural development.